An Effective Triage Education Method for Triage Nurses: An Overview and Update - Zagalioti SC; Ziaka M; Exadaktylos A; Fyntanidou B (Open Access Emergency Medicine)
Sofia-Chrysovalantou Zagalioti,1 Mairi Ziaka,2 Aristomenis Exadaktylos,2 Barbara Fyntanidou1 1Department of Emergency Medicine, AHEPA University General Hospital, Aristotle University of Thessaloniki, Thessaloniki, Greece; 2Department of Emergency Medicine, Inselspital University Hospital, University of Bern, Bern, SwitzerlandCorrespondence: Sofia-Chrysovalantou Zagalioti, Email sofia_zag@yahoo.comBackground: Accurate decision-making in triage largely determines the amount of time required for a patient to be evaluated and treated while in the emergency department. Nursing staff worldwide have similar learning characteristics with similar working hours and common goals, despite the fact that different triage scales are used globally. The aim of this mini review is to present the different educational methods and identify the most effective for triage training of triage nurses.Materials and Methods: We screened studies concerning triage education for nurses in Emergency Department, in databases including PubMed, CENTRAL and CINAHL. From November 12, 2023 to February 15, 2024, databases were searched for relevant literature. “Triage education” OR “triage training” AND “emergency nurses” OR “triage nurses” were the MeSH terms.Results: There are various educational methods, including traditional, web-based, audiovisual, simulation-based, blended learning, and other specialized approaches. Almost all of the studies that are currently available demonstrate how effectively an educational intervention might improve nurses’ comprehension of triage. Except for one, every study concluded that the educational intervention significantly improved nurses’ triage knowledge. Comparing the included studies is challenging due to their heterogeneity, and applying the results in practice requires caution.Conclusion: The majority of studies reported that educational interventions effectively increased nurses’ triage knowledge. Blended learning in conjunction with refresher courses enhanced triage-related knowledge and decision-making; however, additional research is required to ascertain whether this approach is superior to the others and whether these improvements will last.Keywords: educational method, emergency department, triage education